The hsp 16 Gene of the Probiotic Lactobacillus acidophilus Is Differently Regulated by Salt, High Temperature and Acidic Stresses, as Revealed by Reverse Transcription Quantitative PCR (qRT-PCR) Analysis - Daniela Fiocco (International Journal of Molecular Sciences, 2011)
Small heat shock proteins (sHsps) are ubiquitous conserved chaperone-like proteins involved in cellular proteins protection under stressful conditions. In this study, a reverse transcription quantitative PCR (RT-qPCR) procedure was developed and used to quantify the transcript level of a small heat shock gene (shs) in the probiotic bacterium Lactobacillus acidophilus NCFM, under stress conditions such as heat (45 °C and 53 °C), bile (0.3% w/v), hyperosmosis (1 M and 2.5 M NaCl), and low pH value (pH 4). The shs gene of L. acidophilus NCFM was induced by salt, high temperature and acidic stress, while repression was observed upon bile stress. Analysis of the 5' noncoding region of the hsp16 gene reveals the presence of an inverted repeat (IR) sequence (TTAGCACTC-N9-GAGTGCTAA) homologue to the controlling IR of chaperone expression (CIRCE) elements found in the upstream regulatory region of Gram-positive heat shock operons, suggesting that the hsp16 gene of L. acidophilus might be transcriptionally controlled by HrcA. In addition, the alignment of several small heat shock proteins identified so far in lactic acid bacteria, reveals that the Hsp16 of L. acidophilus exhibits a strong evolutionary relationship with members of the Lactobacillus acidophilus group.